Current and Promising Antivirals Against Chikungunya Virus - Friederike I. L. Hucke; Joachim J. Bugert (Frontiers Media S.A., 2020)
Chikungunya virus (CHIKV) is the causative agent of chikungunya fever (CHIKF) and is categorized as a(n) (re)emerging arbovirus. CHIKV has repeatedly been responsible for outbreaks that caused serious economic and public health problems in the affected countries. To date, no vaccine or specific antiviral therapies are available. This review gives a summary on current antivirals that have been investigated as potential therapeutics against CHIKF. The mode of action as well as possible compound targets (viral and host targets) are being addressed. This review hopes to provide critical information on the in vitro efficacies of various compounds and might help researchers in their considerations for future experiments.